PENGARUH FOLLOWERSHIP, KOMITMEN ORGANISASI, DAN ALTRUISM TERHADAP KINERJA PEGAWAI NEGERI SIPIL DI KABUPATEN KEPULAUAN TANIMBAR (STUDI PADA SEKRETARIAT DAERAH) - Betoky , Reimon; Joyosumarto, Subarjo (Journal of Accounting, Management and Islamic Economics, 2025)
Human Resources (HR) has an important role as the driving force of the government organizational system, namely the humans who are in it, namely employees who work within the framework of their duties, functions and responsibilities. Performance in an organization is carried out by all human resources, both elements of leadership and employees. There are so many factors that can influence HR to carry out their performance, namely knowledge and skills, competencies, motivation, commitment, attitudes, and behaviors that can affect their performance. The aims of this study are as follows: (1) to find out the positive and significant influence between followership on the performance of civil servants in KKT. (2) determine the positive and significant effect of organizational commitment on the performance of civil servants in KKT. (3) determine the positive and significant effect of altruism on the performance of civilservants in KKT. (4) determine the positive and significant effect between followership, organizational commitment, and altruism together on the performance of civil servants in KKT. The object of this research is Followership, Organizational Commitment and Altruism as independent variables and Employee Performance as the dependent variable. The design or type of research used is quantitative research with purposive sampling method and using theSlovin formula with a total sample of 170. This study uses primary data and collected by questionnaire technique. The data analysis method used is the Scaling Method of Successful Interval and multiple regression modeling with an ordinary least squares (OLS) estimator. The results of this study can be concluded as follows: (1) There is a positive but not significant effect between the followership variable on the performance variable of civil servants in KKT,(2) on the organizational commitment variable there is a positive and significant influence on the performance of civil servants in KKT, (3) On altruism variable was found to have a positive and significant effect on the performance of civil servants in KKT, (4) The variables of followership, organizational commitment, and altruism together had a positive and insignificant effect on the performance of civil servants in KKT. For future research, it is recommended to consider other factors that also influence employee performance in addition to followership factors, organizational commitment, and altruism, for example work culture, organizational climate, work motivation, and other factors and further research can also broaden the orientation of research on scope of alarger organization or wider population, or conduct research on other local government organizations.